2019
DOI: 10.3390/ijms20112655
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Positive Breast Cancer with High Expression of Androgen Receptor has Less Cytolytic Activity and Worse Response to Neoadjuvant Chemotherapy but Better Survival

Abstract: Estrogen receptor (ER) positive breast cancer (BC), the most abundant BC subtype, is notorious for poor response to neoadjuvant chemotherapy (NAC). The androgen receptor (AR) was reported to support estradiol-mediated ER activity in an in vitro system. Recently, ER-positive BC with fewer tumor infiltrating lymphocytes (TILs) was shown to have a better prognosis, opposite to the trend seen with ER-negative BC. We hypothesized that ER-positive BC with high expression of AR will have fewer TILs and an inferior re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 44 publications
(58 reference statements)
1
54
1
Order By: Relevance
“…Normalized microarray-based tumor gene expression and clinical data for 1903 patients of METABRIC cohort were obtained through the cBio portal, as we previously reported [48][49][50]. For the following studies, normalized microarray-based tumor gene expression and clinical data were obtained from Gene Expression Omnibus (GEO) repository (http://www.ncbi.nlm.ih.gov/geo/): Shi et al…”
Section: Data Of Metabric and Other Breast Cancer Cohortsmentioning
confidence: 99%
“…Normalized microarray-based tumor gene expression and clinical data for 1903 patients of METABRIC cohort were obtained through the cBio portal, as we previously reported [48][49][50]. For the following studies, normalized microarray-based tumor gene expression and clinical data were obtained from Gene Expression Omnibus (GEO) repository (http://www.ncbi.nlm.ih.gov/geo/): Shi et al…”
Section: Data Of Metabric and Other Breast Cancer Cohortsmentioning
confidence: 99%
“…GSEA was performed comparing the high mutation and low mutation tumors, utilizing the Hallmark gene sets 38 with the software provided by the Broad Institute (https:// software.broadinstitute.org/gsea/index.jsp), as described before 20,21,24,39 .…”
Section: Gene Set Enrichment Analysis (Gsea)mentioning
confidence: 99%
“…A meta-analysis by Bozovic-Spasojevic et al employing univariate and multivariate analyses, uncovered that AR expression results in significantly improved disease-free survival (DFS) and OS in ER+ BCs ( 44 ). In one study using transcriptomic data obtained from TCGA and METABRIC cohorts, high AR levels in ER+ BC correlated with fewer tumor-infiltrating lymphocytes and cytolytic activity, as well as far less sensitivity to neoadjuvant chemotherapy, yet better survival ( 45 ). However, a study of 3,021 postmenopausal women with early-stage ER+ BC showed that AR expression was not linked with the prognosis, nor could it predict the response to letrozole or tamoxifen ( 46 ).…”
Section: The Clinical Relevance Of Ar In Bcmentioning
confidence: 99%